2015
DOI: 10.1088/0004-637x/799/2/170
|View full text |Cite
|
Sign up to set email alerts
|

An Ancient Extrasolar System With Five Sub-Earth-Size Planets

Abstract: The chemical composition of stars hosting small exoplanets (with radii less than four Earth radii) appears to be more diverse than that of gas-giant hosts, which tend to be metal-rich. This implies that small, including Earth-size, planets may have readily many -3formed at earlier epochs in the Universe's history when metals were more scarce. We report Kepler spacecraft observations of Kepler-444, a metal-poor Sun-like star from the old population of the Galactic thick disk and the host to a compact system of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
148
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 195 publications
(165 citation statements)
references
References 215 publications
(263 reference statements)
17
148
0
Order By: Relevance
“…Taking into account the fact that planet-hosting stars at low metallicities mostly belong to the Galactic thick disk (Haywood 2008;Adibekyan et al 2012b) one can speculate that the oldest terrestrial planetary systems (e.g. Kepler-444;Campante et al 2015) may have different compositions to the terrestrial solar system planets; however, for the exact derivation of the chemical properties of these planets precise abundances of C and O are also needed 4 . While we already derived oxygen abundance for most of the stars in this sample (Bertran de Lis et al 2015) the derivation of carbon abundances is still in progress (Suárez-Andrés et al, in prep.…”
Section: Discussionmentioning
confidence: 99%
“…Taking into account the fact that planet-hosting stars at low metallicities mostly belong to the Galactic thick disk (Haywood 2008;Adibekyan et al 2012b) one can speculate that the oldest terrestrial planetary systems (e.g. Kepler-444;Campante et al 2015) may have different compositions to the terrestrial solar system planets; however, for the exact derivation of the chemical properties of these planets precise abundances of C and O are also needed 4 . While we already derived oxygen abundance for most of the stars in this sample (Bertran de Lis et al 2015) the derivation of carbon abundances is still in progress (Suárez-Andrés et al, in prep.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most remarkable discoveries so far is Kepler-444, which consists of a K dwarf of age 11.2 ± 1.0 Gyr hosting five sub-Earth-size planets with orbital periods of less than 10 days (Campante et al, 2015). Kepler-444 demonstrated that sub-Earth-size planets have existed for most of the history of our Universe, and the discovery of a pair of low-mass companions in a highly eccentric orbit furthermore showed that the formation of small planets appears to be robust against early truncation of the protoplanetary disk (Dupuy et al, 2016).…”
Section: The Importance Of Precise Exoplanet Radiimentioning
confidence: 99%
“…Old main-sequence systems (e.g. Campante et al 2015), dust and planets around giant branch stars (Bonsor et al 2014;Trifonov et al 2015;Lillo-Box, Barrado & Correia 2016;Wittenmyer et al 2016), and polluted white dwarfs at a variety of cooling ages (Koester, Gänsicke & Farihi 2014;Hollands et al, in preparation) all provide necessary constraints. Main-sequence planetary studies have now begun to utilize white dwarf atmosphere chemical signatures in their planetary formation models (Carter-Bond et al 2012;Morlok et al 2014;Bergin et al 2015;Ramírez et al 2015;Mordasini et al 2016;Spina, Meléndez & Ramírez 2016), and future missions such as PLATO will further enable comparisons with well-constrained stellar ages (Veras et al 2015b).…”
Section: M P O Rta N C E O F D E T E R M I N I N G Fat Ementioning
confidence: 99%